Photoconductivity Relaxation Time in Macroporous Silicon - Volodymyr Fedorovych Onyshchenko; L. A. Karachevtseva; M. I. Karas’ (Ital Publication, 2020)
Macroporous silicon has found applications in sensors, receivers, integrated microchips and solar cells. In this work, we first showed analytically the photoconductivity relaxation time of in macroporous silicon is determined from a system of two transcendental equations. The analytical description of the photoconductivity relaxation model contains the diffusion equation solution both in single crystal substrate and in an effective medium of macroporous layer, as well as boundary conditions recorded for the surfaces of the layer of macroporous silicon and single crystal substrate. We showed that the photoconductivity relaxation time in macroporous silicon rapidly decreases with increasing macropore depth from 0 to 25 μm and reduced thicknesses of the single crystal substrate from 250 to 0 μm. The photoconductivity recombination time in the sample of macroporous silicon is limited by the diffusion of charge carriers from the substrate to the recombination surfaces in the macroporous layer. The system of transcendental equations that we have found will find application in calculating the relaxation time of photoconductivity in macroporous silicon devices such as sensors, receivers, and solar cells.